Ketertarikan lalat buah (Diptera: Teprhidate) pada senyawa atraktan yang mengadung protein dan ketinggian perangkap berbeda pada tanaman jeruk - edra robson; syahrial oemry; Marheni Marheni (Universitas Sumatera Utara, 2019)
ABSTRACT Fruit flies is an important pest for citrus. This research was aimed to determine the effect of (Bractocera dorsalis Hendel.) fruit flies against attractant compounds that contain protein and the height of the trap on the number of catches of fruit flies in the planting of sweet oranges (Citrus sinensis L.). and differences in the sex ratio of fruit flies. This study used a non factorial randomized block design with 9 treatments namely: T0(compound ME 100 cm high), T1(ME compound and cocoa waste 85 cm high), T2(ME compound ME and cocoa waste 135 cm high), T3(ME compound ME and cocoa waste 185 cm high),T4(ME compound and cocoa waste 235 cm high), T5(ME compound and tempe waste 85 cm high), T6(ME compound and tempe waste 135 cm high), T7(ME compound and tempe waste 185 cm high),and T8(ME compound and tempe waste 235 cm high). The results showed that the : type of fruit fly trapped was species of B. dorsalis. In the week four, it was found that the largest population of fruit flies was trapped 155 imago. Treatment cocoa waste was effective in trapping fruit flies in weeks 1-4 with a mean of 12,33 fruit flies and treatment tempe waste trapping fruit flies at week 5 with an average of 8,67 fruit flies. The trap height that is effective at trapping fruit flies is 85 cm. The number of male trapped were 443 males and 19 females with a ratio of 1: 17 and 1 : 26 sex ratio.